Association of 16S and 23S ribosomal RNAs to form a bimolecular complex. - Burma, D P (1983)
Association of the 30S and 50S subunits to generate the 70S ribosomes of Escherichia coli has long been known but the mechanism of this interaction remains obscure. Light-scattering studies indicate that naked 16S and 23S RNAs can also associate under conditions similar to those required for the assembly of ribosomes from the constituent RNAs and proteins. The RNA-RNA association also takes place in the presence of ethanol, which promotes folding of 16S and 23S RNAs into specific compact structures with the morphological features of 30S and 50S ribosomes, respectively. Equimolar amounts of the two RNAs are involved in the association. The formation of a stoichiometric complex was shown by light scattering, sucrose density gradient centrifugation, and composite polyacrylamide/agarose gel electrophoresis. The presence of the two species of RNA in the complex was also shown by gel electrophoresis. The association of naked 16S and 23S RNAs suggests that RNA-RNA interaction may play an important role in the association of 30S and 50S subunits.